Sistema renina-angiotensina nas células da teca e granulosa durante a ovulação e luteinização em bovinos - Dau, Andressa Minussi Pereira (2017)
The objective of present study was to investigate (Pro)renin receptor function in the theca and granulosa cells during the preovulatory period and luteinization in cattle. During the initial preovulatory period, prorenin induced the resumption of oocyte meiosis even in the presence of follicular hemisections or forskolin. In granulosa cells, pró-renina did not increase LHinduced epiregulin (EREG) mRNA after 6 h of culture. Treatment with prorenin plus LH increased amphiregulin (AREG) and prostaglandin synthase 2 (PTGS2) mRNA in granulosa cells. The absence of prorenin effect to stimulate EREG, AREG, and PTGS2 in granulosa cells was established using different combinations of treatments with prorenin and/or aliskiren ([P]RR inhibitor) and/or LH. Treatment of granulosa cells with LH plus EGFR antagonist (AG1478) did not regulate prorenin and (P)RR after 6 h of culture. This result was confirmed in vivo using a model of intrafollicular treatment with AG1478 and intramuscular treatment with GnRH. Finally, (P)RR protein and transcripts for prorenin and pro-fibrotic genes increased in the granulosa cells from 12 h post-GnRH. In the theca cells, (P)RR mRNA and protein increased 6 h after treatment of cows with GnRH. The LH effect to stimulate (P)RR transcript was confirmed in vitro. Intrafollicular treatment with aliskiren did not reduce the ovulation rate. In cultured theca cells, AREG and EREG mRNA were not significantly expressed and ADAM17 was not stimulated by prorenin. Intrafollicular injection of AG1478 did not regulate LH-induced (P)RR, although increased CYP17A1 protein. Prorenin did not induce androstenedione and testosterone synthesis in cultured theca cells. In the corpus luteum, prorenin and (P)RR mRNA were increased at day 10 of estrous cycle compared to day 5, but were not regulated by prostaglandin in vivo, as observed for profibrotic genes. Intrafollicular treatment with aliskiren reduces serum progesterone levels in cows that ovulated. Prorenin role in progesterone synthesis through (P)RR was also evidenced in vitro. Moreover, prorenin induced ERK1/2 phosphorylation in luteal cells, although ERK1/2 inhibition (PD0325901) did not completely inhibit prorenin-induced progesterone synthesis, as evidenced using AG1478. In summary, these results demonstrate that prorenin and (P)RR are stimulated by LH at the end of the preovulatory period and, therefore, they are not related to genes regulated by LH at the initial ovulatory process in granulosa cells; (P)RR is stimulated by LH in the theca cells independently of EGFR; and prorenin stimulate progesterone synthesis through (P)RR, which involves ERK1/2 and EGFR participation. In conclusion, (P)RR is upregulated in granulosa and theca cells after gonadotropins peak and prorenin/(P)RR play an important role in the resumption of oocyte meiosis and on progesterone synthesis in the corpus luteum in cattle.